UV-C treatments extend the shelf life of fresh-cut peppers by delaying pectin solubilization and inducing local accumulation of phenolics - Rodoni, Luis María (2015)
In recent years there has been increased interest in the search of environmentally-friendly treatments that could complement the benefits of proper temperature management in vegetables. In this work we evaluated the effect of UV-C treatments on quality retention of fresh-cut red peppers. To select the most suitable treatment condition red peppers sticks (5 × 1 cm) were UV-C irradiated (1.5; 3; 5; 6; 10 and 20 kJ m⁻²) in the inner (I), outer (O) or both fruit surfaces (I + O). UV-C treatments with 10 kJ m⁻² I + O were the most effective to reduce spoilage and were used for further evaluations. The selected treatment caused no alterations in sugars, color, acidity or antioxidant capacity and markedly reduced decay, weight loss, softening and pectin solubilization. UV-treated fruit also showed lower respiration rate and electrolyte leakage, indicating improved quality maintenance. UV-C exposure did not exert large direct germicide effects. Instead, histochemical analyses showed that the treatments elicited the superficial accumulation of hydroxycinnamic acid-derivatives (OH-CinAD). Overall, results show that UV-C treatments (10 kJ m⁻² I + O) delay pectin solubilization and induce surface accumulation of phenolics and could be useful to complement low temperature storage and extend the shelf life of fresh-cut red peppers.